Fenomena Remaja Menggunakan Media Sosial dalam Membentuk Identitas - Afriluyanto, Tegar Roli (Fakultas Dakwah IAIN Purwokerto, 2017)
Objective of this study is to explore a phenomenon of how social media shapes identity on teen. The research is using Von Eckartsberg phenomenology analysis. Steps used on yhis procedures are data analysis, formed in explication and interpretation. After interview data is completed, last phase of this procedure is to read and meticulously analyzed the data to uncover the meaning configuration, both structure and the processes. Subject of this study is teen, actively using social media, account owner of facebook and twitter. Result of the study shows that each subject has projected different identity on each social media they have. In terms of personal orientation, these teen are using social media to communicate with their peers. This orientation is the reason why these teen have social media account of more than one. Moreover, these teen try to construct positive image on those social media. Their images are often presented as smart, happy by hobbies and leisure they participate. These teen is quite open in showing their identity. It is showed on their photos, words and expression on social media status.